1977
DOI: 10.1111/j.1745-4549.1977.tb00312.x
|View full text |Cite
|
Sign up to set email alerts
|

Storage Stability of Thiamin and Riboflavin in a Dehydrated Food System

Abstract: The storage stability of thiamin mononitrate and riboflavin in a low moisture dehydrated model food system was determined as a function of water activity, moisture content and storage temperature. Fortification of the model system was at a level of 25% RDA per 100 g. The model system was equilibrated at water activities below, at and above the calculated water activity corresponding to the monomolecular moisture content for the adsorption isotherms. Thiamin retention was approximately 100% after eight months s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

1981
1981
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 6 publications
0
12
1
Order By: Relevance
“…The a w corresponding to the m m values are often used in predicting the stability of low‐moisture foods. Systems at these a w conditions were found to have fairly low rates of chemical reactions (Dennison and others 1977) and the lowest rate of lipid oxidation (Nelson and Labuza 1992). However, in amorphous glassy systems, the glass transition behavior may also affect rates of chemical reactions, especially those of diffusion‐controlled reactions (Roos 1995).…”
Section: Resultsmentioning
confidence: 99%
“…The a w corresponding to the m m values are often used in predicting the stability of low‐moisture foods. Systems at these a w conditions were found to have fairly low rates of chemical reactions (Dennison and others 1977) and the lowest rate of lipid oxidation (Nelson and Labuza 1992). However, in amorphous glassy systems, the glass transition behavior may also affect rates of chemical reactions, especially those of diffusion‐controlled reactions (Roos 1995).…”
Section: Resultsmentioning
confidence: 99%
“…Loss of nutrients in dehydrated foods due to temperature, moisture, and oxygen have been reported by many workers. 87 " 90 The packaging of most commercially available dehydrated foods is primarily aimed at the exclusion of water, although exclusion of oxygen is a desired but infrequent practice. 20 Atmospheric packaging is usually used and vacuum and gas flush is practiced for products highly sensitive to oxygen.…”
Section: Initial Moisture (Mmentioning
confidence: 99%
“…Degradation of thiamin generally increased with increasing a w . Dennison et al [34] found similar results in a model system at 45°C; however, at temperatures ≤ 37°C thiamin was found to be quite stable regardless of storage temperature or a w . Thiamin retention was significantly higher in FL pouches.…”
Section: Resultsmentioning
confidence: 71%